Effect of process variables on surface roughness in electrochemical machining of stainless steel 304 - Fadhil Ibrahim, Abbas; Adel Abdullah, Mostafa; Kadhim Ghazi, Safaa; H. Hassoon, O. (International Journal of Engineering and Technology, 2019)
The electrochemical machining process is largely used in industry operations to manufacture components used in automotive, aerospace and medical applications. The optimal conditions of this process can significant reducing the electrochemical machining operating, maintenance cost, tooling, and producing of components with high accuracy. The more requirements of the processes are that work piece must be electrical conduct. Due to various independent variables in this process, difficulties are presented in the chosen and analysis of the experimental results. In this work, the response surface methodology and analysis of variance method are applied to optimize ECM process and to study the more effective parameters (current, inter- electrode gap, and concentration of electrolyte) on surface roughness of stainless steel 304 workpiece. An empirical equation formula is proposed based on the experimental results and the statistical model that used to predict the surface roughness. The R2 (ability the Input variables to prediction the output variables) of the predictive model was 92.6%. The experimental results were shown that the current considered the most effective factor to minimize the Ra, while the electrolyte concentration considered the second affect factor.Â